Study Design Selection in Early Clinical Anti‐Hyperglycemic Drug Development: A Simulation Study of Glucose Tolerance Tests - Moustafa M. A. Ibrahim; Siti M. S. Ghadzi; Maria C. Kjellsson; Mats O. Karlsson (Wiley, 2018)
In antidiabetic drug development, phase I studies usually involve short‐term glucose provocations. Multiple designs are available for these provocations (e.g., meal tolerance tests (MTTs) and graded glucose infusions (GGIs)). With a highly nonlinear, complex system as the glucose homeostasis, the various provocations will contribute with different information offering a rich choice. Here, we investigate the most appropriate study design in phase I for several hypothetical mechanisms of action of a study drug. Five drug effects in diabetes therapeutic areas were investigated using six study designs. Power to detect drug effect was assessed using the likelihood ratio test, whereas precision and accuracy of the quantification of drug effect was assessed using stochastic simulation and estimations. An overall summary was developed to aid designing the studies of antihyperglycemic drug development using model‐based analysis. This guidance is to be used when the integrated glucose insulin model is used, involving the investigated drug mechanisms of action.